Resistance mechanisms and prospects of trastuzumab - Wang, Lizhe; Wang, Yu; Li, Yueyang; Zhou, Li; Du, Jiahui; Wang, Jin; Liu, SiHan; Cao, Yongyi; Li, Yuzhi; Yang, Wenying; Zhu, Ting (Frontiers in Oncology, 2024)
Breast cancer that overexpresses Human Epidermal Growth Factor Receptor 2 (HER2+) due to gene amplification or overexpression constitutes 15-20% of all breast cancer cases. Trastuzumab, the first FDA-approved monoclonal antibody targeting HER2, serves as the standard first-line treatment for HER2-positive advanced breast cancer, as recommended by multiple clinical guidelines.Currently, accumulated clinical evidence reveals a considerable degree of variability in the response of HER2+ breast cancer to trastuzumab treatment. Specifically, over 50% of patients either do not respond to or develop resistance against trastuzumab.The specific mechanisms of resistance to trastuzumab are currently unclear. This paper aims to review the existing research on the resistance mechanisms of trastuzumab, based on its target, from aspects such as genetic loci, molecular structure, signaling pathways, and the tumor microenvironment and to outline current research progress and new strategies.